2015
DOI: 10.1103/physrevb.91.165418
|View full text |Cite
|
Sign up to set email alerts
|

Sputter yield of curved surfaces

Abstract: The mean sputter yield produced by the impact of a single ion depends on the radii of curvature of the target surface at the point of impact. Using the Sigmund model of ion sputtering, we develop analytical formulae for this dependence for the case in which the radii of curvature are large compared to the size of the ion-induced collision cascade; both locally perpendicular and oblique ion impact are considered. The sputter yield is increased for impact on convex surfaces. The influence of surface curvature al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
3
27
0
1
Order By: Relevance
“…SRIM is not a dynamic code, it consider every atomic layer as fresh without considering the effect of previous bombardment this can slightly change the sputtering yield based on surface conditions. 33,34 These results validate the QCM measurement system with the assumption that sticking of Si atom is one while condensing on QCM surface. Figure 4 shows volumetric sputtering yield profiles for various ion energies based on QCM measurements for BN using Xenon ion beam energies of 100 eV (Fig.…”
Section: E Qcm Data Validationsupporting
confidence: 65%
“…SRIM is not a dynamic code, it consider every atomic layer as fresh without considering the effect of previous bombardment this can slightly change the sputtering yield based on surface conditions. 33,34 These results validate the QCM measurement system with the assumption that sticking of Si atom is one while condensing on QCM surface. Figure 4 shows volumetric sputtering yield profiles for various ion energies based on QCM measurements for BN using Xenon ion beam energies of 100 eV (Fig.…”
Section: E Qcm Data Validationsupporting
confidence: 65%
“…In addition, to make a theory of the pattern formation, the dependence of the sputter yield on the surface curvature at the point of impact is needed [21]. Recent work has shown that even though the Sigmund model does not do particularly well in predicting the sputter yield of a flat surface, it does much better in describing how the sputter yield changes as the surface curvature is increased provided that the curvature is not too large [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, experiments invariably show that the sputter yield at first increases with θ, but then attains a maximum before falling to zero at grazing incidence. It is therefore remarkable that the Sigmund model does quite well in predicting how the sputter yield depends on the surface curvature if the angle of incidence is not too close to grazing and the radii of curvature are not too small [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The SBE is conventionally set to the enthalpy of sublimation in the present case for Si to the bulk value of 4.7 eV. 6,7 The limitations of this approximation are already discussed in the original publication. 20 The accuracy with which Monte Carlo (such as SRIM, 1 iradina, 11 SDTrimSP 21 and TRIDYN 22 ) codes can quantitatively predict sputtering depends on the correct SBE and the correct interaction potential between the atoms and ions within the target, especially at low collision energies.…”
mentioning
confidence: 99%